Listeners’ Preferences about Different Components of Farm Broadcast Programmes (Indian Journal of Extension Education, 2018)
The study aims to know the listeners’ preferences towards different components of farm broadcast programmes under the penetration range of Patna Akashvani Kendra of Bihar state. Asample of 60 radio listening farmers was randomly drawn from two blocks and data were collected through the pre-tested interview schedule. The findings suggest that majority of the radio listening respondents were satisfied with the present timing of the farm broadcast. Maximum percentage of the respondents preferred the frequency of farm broadcast to be daily and a duration of 45 minutes. The findings revealed that Agricultural programme, News and Pitara were the most preferred radio programmes in order of their preference. The study showed that the crop production and farm machinery were the most and least preferred areas respectively towards various subject matter concerning in the field of agriculture. The interview with progressive farmers was the most preferred mode of presentation whereas straight talk was the least one as revealed by the selected respondents.